INNOVATIVE AND CONVENTIONAL APPROACHES TO TEACHING ENGLISH FOR SPECIFIC PURPOSES. - Nasirova R.A. SamSIFL (Western European Studies, 2025)
This article explores various methods of teaching English for Specific Purposes (ESP), emphasizing the balance between conventional and innovative approaches. The study highlights the key objectives of ESP teaching, focusing on the development of language competencies required for professional and academic contexts. The role of the teacher in shaping students’ linguistic proficiency is examined, with an emphasis on selecting appropriate teaching materials, designing effective curricula, and maintaining student motivation. Additionally, the article analyzes the significance of integrating traditional methods, such as structured grammar instruction and textbook-based learning, with innovative techniques, including interactive learning, case-based methods, and digital resources. The importance of psychological and pedagogical factors in method selection is also considered, particularly in tailoring instruction to students with varying levels of knowledge
Keywords: methods of teaching; online resources; traditional methods